PENGABDIAN KEPADA MASYARAKAT MELALUI SOSIALISASI PENCEGAHAN STUNTING DI PONDOK PESANTREN TAHFIDZUL QUR’AN DESA SUNGAI PINANG - Islami, Deri; Budianto, Agus; Ramadhan, Rehan Sasli; Irfan, Nur; Latiffunnisa, Husna; Indrawani, Dali; Rudiansyah, Rudiansyah; Mahera, Rafika; Lilianti, Putri (Komunitas Manajemen Kompetitif, 2023)
Stunting cases in Indonesia are considered to have started to decline, reaching 21.6%. This figure is still in a category that has begun to decline from the WHO standard of 20%. The stunting prevalence rate in Riau Province is 17%, although Riau's stunting rate is better than before (21.6%), there are still areas with stunting prevalence rates that need to be prevented, including in the Kampar Regency area in Sungai Pinang Village which is 17 .8%. The aim of this service is to increase the knowledge of the Tahfidzul Qur'an Islamic Boarding School community in Sungai Pinang Village, Kampar Regency regarding stunting prevention. The method used is interactive lectures and questions and answers. The results of the outreach show that public knowledge about stunting is 25:20 who know about stunting. The impact of this service was an increase in the knowledge of counseling participants during the pre-test with a ratio of 25:20. For this reason, it is recommended to the community, especially Islamic boarding school students, to be able to implement the knowledge gained as a form of stunting prevention in the surrounding community by fulfilling nutritional requirements during pregnancy, childbirth and children before the age of 2 years.